Digitalization of Gayo Language: Development of Android-Based Interactive Dictionary Application - Defri Salwan; Desvina Yulisda; Rizky Putra Fhonna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The Gayo language is one of Indonesia’s local cultural treasures that must be preserved, especially considering the declining use of regional languages among the younger generation. This study aims to develop an Android-based Gayo Language Dictionary application as an interactive learning medium that is easily accessible to the public. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, eval_uation). The Gayo vocabulary data was obtained from official documents published by the Ministry of Education and Culture and other related institutions. The application was developed using the Kotlin programming language on Android Studio, with Supabase as the database and Firebase Authentication for user login. The main features of the application include bidirectional translation, word search, favorite marking, and historical information about the language. Testing results showed that all features performed well based on smoke testing and user acceptance testing (UAT). The application received an average score of 81% for functionality, interface, and content; 79% for system performance; and the highest score of 85% for user satisfaction. In conclusion, the Gayo Language Dictionary application has proven to be an effective tool for language learning and preservation through a modern technological approach.